2018
DOI: 10.1103/physrevb.98.121409
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics of epitaxial strain-free interfaces

Abstract: We report a systematic lattice dynamics study of the technologically important Fe 3 Si/GaAs heterostructure for Fe 3 Si layer thicknesses of 3, 6, 8, and 36 monolayers. The Fe-partial phonon density of states obtained by nuclear inelastic scattering exhibits up to a twofold enhancement of the low-energy phonon states compared to the bulk material for layer thicknesses of 8 monolayers and below. First-principles calculations explain the observed effect by interface-specific phonon states originating from the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 53 publications
2
25
0
1
Order By: Relevance
“…Combined experimental and theoretical studies of strainfree metal/semiconductor heterostructures 42 and metallic multilayers 43 demonstrated that the force constants of the atoms located at the interface are drastically reduced compared to the bulk values. This gives rise to an entirely different PDOS of the interface layers from that of a bulk material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined experimental and theoretical studies of strainfree metal/semiconductor heterostructures 42 and metallic multilayers 43 demonstrated that the force constants of the atoms located at the interface are drastically reduced compared to the bulk values. This gives rise to an entirely different PDOS of the interface layers from that of a bulk material.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, up to a two-fold enhancement of the number of low-energy states along the interface was measured and theoretically confirmed for the strain-free Fe 3 Si/GaAs interface. 42 Due to the grazing-incidence scattering geometry used in our experiment we determine the in-plane projected PDOS. Therefore, the observed discrepancy between experiment and theory up to 5 meV and between 12 and 15 meV most likely originates from the EuO/YAlO 3 interface-specific PDOS.…”
Section: Methodsmentioning
confidence: 99%
“…For variant C, the features entail a remarkable agreement between model and experiment. In general, variant C leads to the lowest residual sum squared (values in Table IV are normalized to variant C) and yields the best agreement with the expected A value of 0.14 [46]. The deviations between experiment and theory observed for all variants in the range 17-27 meV may arise from the additional phonon modes induced by the Ge/Fe 3 Si interface that is not accounted for by the model.…”
Section: Resultsmentioning
confidence: 79%
“…with g if (E, Q if ) and g bulk (E, Q bulk ) being the calculated [46]). Furthermore, due to the grazing incidence geometry of the experiment, only the in-plane PDOS is measured, which allows for a comparison with the calculated xy-projected PDOS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation